Education and Free Education: A Reading to Paulo Freire'sCritical Pedagogy (Raparin Journal of Humanities (RJH), 2025)
The notion of free education goes back to ancient Greece, and it has been playing a significant role in developing studying programs in various western educational systems. Paulo Freire has put importance on freedom in education, particularly in the third world. Through his philosophical theories, Freire has tried to spread and develop the notion of freedom in education; especially, raising the awareness of the oppressed classes towards the oppression that is done against them, and eradicating social classes to achieve social justice and making freedom.  This study discusses the critical pedagogy and the banking method in the educational philosophy of Paulo Freire, the Brazilian libertarian, and it analyses the main concepts, such as education for freedom, banking method vs. critical pedagogy, the role of dialogue and teachers. The method of this study relies on analyzing the works of Freire, with focus on his book; The Pedagogy of the Oppressed, and evaluates the effectiveness of his ideas on the theory and practice of education. The results indicate that Freire's philosophy still continues to insert its importance and influence for fighting educational inequalities and empowering students in the modern educational system. The study gives suggestions about the way of using Freire's viewpoints in the philosophy of education for encouraging social change and establishing a more just society. Among these are developing critical thinking among students, getting rid of conventional education; and bringing about an education that students' abilities are to be developed in it and guarantees freedom and social justice through education.